2009
DOI: 10.1227/01.neu.0000354350.88899.07
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of and Training for Cerebral Aneurysm Clipping With 3-Dimensional Models

Abstract: Some reports have addressed the use of three-dimensional (3-D) models in simulated clipping of cerebral aneurysms. To report on the effectiveness of these models, for this study, we developed two types of 3-D models for use in clipping simulations and for clarifying angioarchitecture and surgical approaches. The two types of model, one made of acrylic polymer and the other made of hollow silicone, were fabricated with a 3-D printer using data obtained with 3-D digital subtraction angiography (3D-DSA). The holl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
127
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 14 publications
0
127
0
Order By: Relevance
“…2,4,5,9,10,12) Kimura et al 7) described preoperative simulations for cerebral aneurysm clipping with 3D models. Although this is a single case, we demonstrated that preoperative endovascular simulations using patient-specific vascular models are also feasible and helpful for designing a treatment strategy and may reduce the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5,9,10,12) Kimura et al 7) described preoperative simulations for cerebral aneurysm clipping with 3D models. Although this is a single case, we demonstrated that preoperative endovascular simulations using patient-specific vascular models are also feasible and helpful for designing a treatment strategy and may reduce the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-specific vascular silicone models are made using cadaver specimens 3,6,9) or three-dimensional (3D) vascular images of patients. 1,7,11) Kimura et al 7) described preoperative simulations for cerebral aneurysm clipping with 3D models. We report, for the first time, preoperative endovascular simulations for cerebral aneurysms using a patientspecific silicone model.…”
Section: Introductionmentioning
confidence: 99%
“…These models were very useful in deciding how to apply clips to occlude the closure line of the aneurysm and combination of aneurysm clips for complex-shaped aneurysms. 11) Electrophysiological monitoring: Electrophysiological monitoring is essential to reduce operative complications. Motor evoked potential monitoring is very useful for reducing managing morbidity during aneurysm surgery, especially around the perforating branches such as the anterior choroidal, posterior communicating, M 1 , and vertebro-basilar arteries.…”
Section: Standards In Managing Unruptured Intracranial Aneurysmsmentioning
confidence: 99%
“…Not only the number (quantity) but also the diversity (quality) of cases may become so limited as to endanger, frustrate, or even make it impossible to secure the objective of mastering the surgical technique required in the surgical treatment of aneurysms. Adaptation to this new reality has prompted technology and imagination with new solutions, such as the development of software applications, surgical simulators, and even prototype models of diseased vessels [6]. These alternatives tend to recreate the problems and gestures one is usually faced with when performing a real surgery, allowing for some part of the necessary training to be acquired on a dummy model and not at the cost of the patient, thereby shortening the surgical caseload learning curve.…”
mentioning
confidence: 99%
“…Unfortunately, these techniques are still at an early stage of development and their application remains quite variable depending on the type or surgical act [2,6].…”
mentioning
confidence: 99%